ZERO WASTE INNOVATION: PEMANFAATAN LIMBAH KULIT PISANG UNTUK PENGUATAN USAHA MIKRO DI DESTINASI WISATA TAWANGMANGU KABUPATEN KARANGANYAR - Panjaitan, Ingrid; Purba, Ika Rosenta; Gunawan, Inge; Damardjati, Fx (Jurnal Pengabdian Bukit Pengharapan, 2025)
This community service initiative aims to enhance awareness and skills among the local population in Tawangmangu Subdistrict, Karanganyar Regency, Central Java, Indonesia, in utilizing banana peel waste as a raw material for high-value economic products. As the leading banana-producing area in the regency, contributing tens of thousands of quintals in 2024 (Badan Pusat Statistik Kabupaten Karanganyar, 2025; Pantura Post, 2025a), Tawangmangu faces significant challenges in managing organic waste that poses risks of environmental pollution. Employing an entrepreneurship-based approach, the program trained participants to process banana peels into liquid organic fertilizer (POC), jam, and healthy snacks such as pudding and crackers, thereby promoting circular economy principles and zero-waste practices. Results demonstrated a 75% increase in participants’ knowledge and the potential for additional income through the sale of processed products. This activity contributes to sustainable development in the Tawangmangu tourism area.